Relationship Of Village Chief Leadership And Village Construction In Minahasa Region - Langingi, Julius (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
Minahasa regency consists of twenty seven subdistrics, 495 villages, with the population of 70.459 people.  These people live in 474 villages each of which headed by a village head.  In order to have the process of village continous development on with such a power at rooted in the society, each village needs a creative leader.  The progress and the growth of the village will depend on the leadership of its village head, in estimating and utilizing the resources and the assets found in the village.  In anticipation of this issue, the village heads needs be creative that will enable him, to disearer all the resources for development.  The developmen factors, and the decision maker or a leader are basically interrelated, in explaining an innovation.  This study aimed to investigate the age, educational background factor, and experiences as village chief relationship and wanted to know its relationship to the village of rural development, that include the degree of village income in 15 villages in the 3 subdistricts namely, the Ratahan District, the Tombariri Distric and the Dimembe district, Minahasa Regency.  Testing hypotesis in this research was formulated as follows:  There are relationship between age, education and experiences of village chief leadership in Upgrading of village development.  This research was carried out in away of random samplw toward 135 respondents in 3 subdistricts mentioned above and used questionnaires as tools of measurment and the data was analized using Chi-Quadrant statistical techniques.  Analitical result show that hypotesis was proved true on the level of significance 1% and 5 %.  The result of this research shows that there are relationship between and educational factor of the village chief leadership and the achievements, of the Village.  There are also relationship  between the experience factor of the village chief leadership and the increase of village achievements.  The village achievements include the increase of village income, village work program, and the village economic development in 15 villages within 3 researched subdistricts.